2009
DOI: 10.1097/sap.0b013e31818937ee
|View full text |Cite
|
Sign up to set email alerts
|

Pedicled Perforator Flaps

Abstract: Described in this study is a surgical concept that supports the "consider and use a pedicled perforator flap whenever possible and indicated" approach to reconstruct a particular skin defect. The operation is entirely free-style; the only principle is to obtain a pedicled perforator flap to reconstruct the defect. The perforators are marked with a hand-held Doppler probe and multiple flaps are designed. The appropriate flap is elevated after identifying the perforator(s). Dissection of the perforator(s) or com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This means that most soft tissue defects have at least one potential skin flap around them. Pedicled perforator flaps can be transferred to the recipient site in many different configurations, with these flaps being called advancement, rotation, transposition and propeller flaps [5][6][7]. Kroll and Rosenfield first introduced the pedicled perforator flap concept for the reconstruction of posterior midline defects in 1988 [8].…”
Section: Discussionmentioning
confidence: 99%
“…This means that most soft tissue defects have at least one potential skin flap around them. Pedicled perforator flaps can be transferred to the recipient site in many different configurations, with these flaps being called advancement, rotation, transposition and propeller flaps [5][6][7]. Kroll and Rosenfield first introduced the pedicled perforator flap concept for the reconstruction of posterior midline defects in 1988 [8].…”
Section: Discussionmentioning
confidence: 99%
“… Pedicled perforator flaps allow defects to be covered with the most appropriate tissue in terms of the composition, shape and location of the defect. A number of studies concerning the covering of pressure sores with perforator flaps have shown that they are a reliable treatment modality. …”
Section: Discussionmentioning
confidence: 99%
“…(14) A number of studies concerning the covering of pressure sores with perforator flaps have shown that they are a reliable treatment modality. (7,8,10,(13)(14)(15)(16)(17) The propeller flap concept was described by Hyakusoku et al in 1991. (4) The term 'propeller perforator flap' was first used in the coverage of ischial and trochanteric pressure sores by Hallock in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to create a flap wherever a musculocutaneous perforator is located . Pedicled perforator flaps allow defects to be covered with the most appropriate tissue in terms of the composition, shape, and location of the defect . The experimental perforator flap model was first described by Okşar et al in 2001.…”
Section: Discussionmentioning
confidence: 99%